Harnessing genomics to fast-track genetic improvement in aquaculture - Houston, Ross D; Bean, Tim P; Macqueen, Daniel J; Gundappa, Manu Kumar; Jin, Ye Hwa; Jenkins, Tom L; Selly, Sarah Louise C; Martin, Samuel A M; Stevens, Jamie R; Santos, Eduarda M; Davie, Andrew; Robledo, Diego (Nature reviews. Genetics, 2020)
Aquaculture is the fastest-growing farmed food sector and will soon become the primary source of fish and shellfish for human diets. In contrast to crop and livestock production, aquaculture production is derived from numerous, exceptionally diverse species that are typically in the early stages of domestication. Genetic improvement of production traits via well-designed, managed breeding programmes has great potential to help meet the rising seafood demand driven by human population growth. Supported by continuous advances in sequencing and bioinformatics, genomics is increasingly being applied across the broad range of aquaculture species and at all stages of the domestication process to optimize selective breeding. In the future, combining genomic selection with biotechnological innovations, such as genome editing and surrogate broodstock technologies, may further expedite genetic improvement in aquaculture.